PERANCANGAN GROUNDING UNTUK LABORATORIUM TEKNIK TEGANGAN TINGGI DI TEKNIK ELEKTRO UNIVERSITAS ISLAM INDONESIA - Wahyudi Budi Pramono; Suyamto Suyamto; Dimas Satriyo Prabowo (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Grounding is used as a protection equipment so as to prevent damage and protection for laboratory users. In designing the grounding must consider the economic aspect and simplicity. Viewed from the side economics and simplicity grounding rods forms that will be used in the design of grounding are multiple ground rods. Because the design is simple but can be obtained low resistance values. This grounding design used two wells which have different parameters, and the resulting R1 = 0.892 Ohm and R2 = 1.5414 Ohm. Because the first well has a smaller resistance value, it will be more effective and efficient when the final draft of grounding used two wells which have the same parameters as the first well, which then shunt connected that the smaller the resistance value amounting to 0.446 Ohm. In the design of the two wells used eight rod electrodes with a diameter of 16 mm and a length of each rod 1 meter. The resulting resistance value is very good to use as the installation of grounding in High Voltage Engineering Laboratory. To obtain a low resistance value is influenced by many factors, such as soil resistivity, a long electrode, the electrode fingers and multiplication factor.